The Mate Screening Motive: How Women Use Luxury Consumption to Signal to Men - Chen, Qihui; Wang, Yajin; Ordabayeva, Nailya (Journal of Consumer Research, 2023)
Abstract Previous research has found that for men, activating a mating motive increases luxury consumption as a way to attract a romantic partner. However, little is known about the role of luxury consumption in women’s romantic endeavors. The present research conceptualizes a mate screening motive, which explains how women use luxury consumption to romantically signal to men. Six studies and two follow-ups conducted in controlled and field settings show that the mate screening motive boosts women’s consumption of luxury goods as a way to signal their mating standards to men and thereby deter undesirable pursuers. The effect is diminished when mate screening is less necessary such as when external screening tools are available (e.g., screening filters on dating websites), the quality of potential mates is high, and the focus is on selecting a desirable partner rather than deterring undesirable pursuers. The findings have important implications for understanding how consumers use products and brands in romantic relationships and for designing marketing strategies and communication for luxury brands, commercial dating services, and dating apps. Our findings also provide insights for consumers on how to use brands and products as effective communication devices in romantic endeavors.